Unicidade e discretização para problemas de valor inicial - Nascimento, Marcio Lemos do (2013)
This paper has two objectives: (i) conducting a literature search on the criteria of uniqueness of solution for initial value problems of ordinary differential equations. (ii) a modification of the method of Euler that seems to be able to converge to a solution of the problem, if the solution is not unique